Serine-Arginine Protein Kinase SRPK2 Modulates the Assembly of the Active Zone Scaffolding Protein CAST1/ERC2 - Arancibia, Duxan; Lira, Matias; Cruz, Yocelin; Barrera, Daniela P.; Montenegro-Venegas, Carolina; Godoy, Juan A.; Garner, Craig C.; Inestrosa, Nibaldo C.; Gundelfinger, Eckart D.; Zamorano, Pedro; Torres, Viviana (My University, 2019)
Neurons release neurotransmitters at a specialized region of the presynaptic membrane, the active zone (AZ), where a complex meshwork of proteins organizes the release apparatus. The formation of this proteinaceous cytomatrix at the AZ (CAZ) depends on precise homo- and hetero-oligomerizations of distinct CAZ proteins. The CAZ protein CAST1/ERC2 contains four coiled-coil (CC) domains that interact with other CAZ proteins, but also promote self-assembly, which is an essential step for its integration during AZ formation. The self-assembly and synaptic recruitment of the Drosophila protein Bruchpilot (BRP), a partial homolog of CAST1/ERC2, is modulated by the serine-arginine protein kinase (SRPK79D). Here, we demonstrate that overexpression of the vertebrate SRPK2 regulates the self-assembly of CAST1/ERC2 in HEK293T, SH-SY5Y and HT-22 cells and the CC1 and CC4 domains are involved in this process. Moreover, the isoform SRPK2 forms a complex with CAST1/ERC2 when co-expressed in HEK293T and SH-SY5Y cells. More importantly, SRPK2 is present in brain synaptic fractions and synapses, suggesting that this protein kinase might control the level of self-aggregation of CAST1/ERC2 in synapses, and thereby modulate presynaptic assembly.
Keywords: active zone; cast1/erc2; coiled-coil; self-aggregation; srpk; synapse